Spectrophotometric Determination of Toxic Elements (Cadmium) in Aqueous Media - Ullah, MR; Haque, M Enamul (Journal of Chemical Engineering, 2011)
Trace amount of toxic element (Cadmium) was determined by spectrophotometer method using 1, 2-dihydroxy anthraquinone-3-sulphonic acid, sodium salt. (Alizarin red S) as a new spectrophotometer reagent. Alizarin red S reacts in slightly acidic solution (0.005 - 0.05M H2SO4) with cadmium to give a deep greenish yellow chelate which has an absorption maximum at 422 nm. The reaction is instantaneous and absorbance remains stable for over 24hrs. The average molar absorption co-efficient and sandell's sensitivity were found to be 2.24 103L mol-1 cm-1 and 20 ng cm 2 of Cd respectively. Linear calibration graphs were obtained for 0.1 - 40μg mL-1 of Cd. The stoichiometric composition of the chelate is 1 : 2 (Cd : Alizarin red S). Large excess of over 50 cations, anions, and some common complexing agents (e.g EDTA, oxalate, citrate phosphate, thio-urea, SCN-) do not interfere in the determination. The method was successfully used in the determination of cadmium in Several Standard Reference Materials (alloys, steels and water) as well as in some environmental waters (In land and surface), biological samples (human blood and urine), soil samples and complex synthetic mixtures. The method has high precision and accuracy. (S = ±0.01 for 0.5 μg mL-1. Keywords spectrophotometry; cadmium determination; 1, 2-dihydroxy anthraquinone-3-sulphonic acid; sodium salt (Alizarin red S); alloy; steel; environmental; biological; samples; soil samples DOI: 10.3329/jce.v25i0.7233 Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.1-12